Jurisdiction Issues in International Tort Litigation: A Singapore View - Yeo, Tiong Min (Institutional Knowledge at Singapore Management University, 1995)
This article looks at the issues that arise at a jurisdictional stage when a claim in tort containing foreign elements is made in a Singapore court. In particular, the amended Order 11 rule 1(f) of the Rules of the Supreme Court is examined. Because of the paucity of local authorities, extensive references are made to relevant Commonwealth cases to aid in the interpretation of the local provision.